2014
DOI: 10.1007/s00259-014-2837-0
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluorocholine PET/CT for localization of hyperfunctioning parathyroid tissue in primary hyperparathyroidism: a pilot study

Abstract: (18)F-Fluorocholine PET/CT appears to be a promising, effective imaging method for localization of hyperfunctioning parathyroid tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(133 citation statements)
references
References 15 publications
10
116
2
5
Order By: Relevance
“…Our data are in agreement with early series that have found high sensitivity of dualisotope scintigraphy with pinhole imaging in detection of MGD defined on the basis of parathyroid four-gland identification (18,24). Head-to-head comparison between 123 I/ 99m Tc-sestamibi PS and the recently introduced 18 F-fluorocholine PET/CT in a large series of pHPT, including medico-economic aspects, will be of particular interest (25,26).…”
Section: European Journal Of Endocrinologysupporting
confidence: 91%
“…Our data are in agreement with early series that have found high sensitivity of dualisotope scintigraphy with pinhole imaging in detection of MGD defined on the basis of parathyroid four-gland identification (18,24). Head-to-head comparison between 123 I/ 99m Tc-sestamibi PS and the recently introduced 18 F-fluorocholine PET/CT in a large series of pHPT, including medico-economic aspects, will be of particular interest (25,26).…”
Section: European Journal Of Endocrinologysupporting
confidence: 91%
“…The authors of the present study have observed that the medians of pre-operative PTH concentrations in patients with PHPT range from 83 to 434 pg/mL [11][12][13][14][15]. Cheon et al observed that there is a statistically significant difference between PTH concentrations in blood serum of patients with parathyroid adenoma and with parathyroid cancer.…”
Section: Discussionmentioning
confidence: 68%
“…7 Recently, dynamic contrast-enhanced CT imaging and choline PET/CT imaging have been advocated to identify parathyroid adenomas if conventional imaging was negative. [8][9][10][11][12][13] Normally functioning parathyroid glands are not seen on choline PET images, but occasionally incidental parathyroid adenomas are found in patients undergoing prostate cancer staging with choline PET, and hitherto unnoticed primary hyperparathyroidism is revealed. 11,14,15 Secondary hyperparathyroidism and tertiary hyperparathyroidism most often result in asymmetrical parathyroid gland hyperplasia and only subtle glandular enlargement, as seen in our case.…”
Section: Figurementioning
confidence: 99%